Building Imaginative Character through Musical Storytelling Methods to Enhance Elementary School Students’ Creativity - Muh. Ferisyal Pratama; Nisa Sri Maulani; Maulida Diah A; Faisal Rahmat Permana (Jurnal Pedagogi dan Pembelajaran, 2025)
Learning in elementary schools still tends to use teacher-centered learning methods with an approach that emphasizes memorization and reproduction of information. This can hinder the development of students' creativity and imagination. This study aims to analyze the effectiveness of the musical storytelling method in enhancing the imaginative character and creativity of elementary school students. The research method used is a quasi-experiment with a static group pretest-posttest design. The sample was selected using purposive sampling. The experimental class and control class each consisted of 15 students. Data collection instruments used tests. Data analysis techniques used quantitative and qualitative analysis. The results of the t-test analysis showed that there was a significant difference between the experimental class and the control class. The average post-test score of the experimental class after the treatment was 85, while the average post-test score of the control class was 80. This proves that the musical storytelling method can improve the imaginative character and creativity of elementary school students. The results of this study indicate that learning using musical storytelling has higher learning outcomes compared to learning using non-musical storytelling. The implication of this study is that learning using musical storytelling can be used to enhance creativity, imagination, and learning outcomes.